Resource Perceptions and Employee Well-Being during the Covid-19 Pandemic: The Role of Personal Control as a Moderator - Yamini Jha; Sanjeev Jha (International Journal of Business and Society, 2022)
This paper used Hobfoll’s conservation of resources (COR) theory to investigate the extent to which interpersonal and financial resources predict the well-being of salaried employees in the United States. Data were collected from a nationally representative survey of adults in the United States conducted by the RAND Corporation . Two measures of well-being (depressive symptoms and life satisfaction), along with an actual loss of financial resources and a perceived lack of interpersonal and financial resources, were examined. The role of perceived control as a moderator in the relationship between resource deficit perceptions and well-being was also examined. The results of the regression analysis indicate that the perceived lack of resources was associated with a decline in well-being. Perceived control was found to buffer the negative effects of resource deficit perceptions. Employees with high levels of perceived control showed less of a reduction in well-being than those with low levels of perceived control as the perceived deficit of resources increased. The study also revealed that actual loss of resources, measured as a decrease in wages, is associated with a decrease in life satisfaction but is not associated with depressive symptoms. We conclude by discussing the theoretical and practical implications of our research on the relationship between resource deficits and well-being during a public health crisis.